2020
DOI: 10.2147/ott.s230478
|View full text |Cite
|
Sign up to set email alerts
|

<p>Urgent Chemotherapy Successfully Rescues a Near Death Patient of Acute Intracranial Hypertension Caused by Intracranial Myeloid Sarcoma</p>

Abstract: Intracranial myeloid sarcoma is a very rare disease with poor prognosis. We report a case of a 28-year-old male patient who was admitted with intense headache, vision disturbance and severe vomiting in June 2017. He had a history of neurosurgical tumor resection operation in April 2017, and the pathological diagnosis was intracranial myeloid sarcoma. Bone marrow aspirate and biopsy had been conducted in May 2017, which demonstrated 5.5% blasts expressing CD13, CD33, CD34, CD117 and MPO, and the cytogenetic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Lontos et al [ 20 ] found no significant difference in the OS of iMS patients between those with localized treatment plus upfront chemotherapy and those with localized treatment alone. For patients with a heavy tumor burden or in poor health, urgent chemotherapy or radiotherapy might be the preferred option [ 10 , 21 , 22 ]. For refractory/relapsed patients, the treatments should include hematopoietic stem cell transplantation and targeted therapy, such as with IDH and FLT-3 inhibitors [ 23 – 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lontos et al [ 20 ] found no significant difference in the OS of iMS patients between those with localized treatment plus upfront chemotherapy and those with localized treatment alone. For patients with a heavy tumor burden or in poor health, urgent chemotherapy or radiotherapy might be the preferred option [ 10 , 21 , 22 ]. For refractory/relapsed patients, the treatments should include hematopoietic stem cell transplantation and targeted therapy, such as with IDH and FLT-3 inhibitors [ 23 – 25 ].…”
Section: Discussionmentioning
confidence: 99%